Membangun Sistem Partisipatif Pengendalian Perilaku-Nyampah Pengunjung Taman Wisata - Zuska, Fikarwin; Agustrisno, Agustrisno; Delvian, Delvian; Zulkifli, Zulkifli (Universitas Medan Area, 2024)
The behavior of visitors littering in coastal tourist parks has resulted in the generation of plastic waste, which, in turn, poses a significant risk of polluting the ocean. This issue arises due to the absence of a deliberately constructed visitor littering control system by the park management. This paper explains that a visitor littering control system in tourist parks can be established by the management through participatory and persuasive approaches, without causing resistance from visitors. The method employed is through active engagement. Park managers and staff across all levels, particularly those who interact directly with visitors, are collaboratively involved in developing a shared understanding. This is achieved through Focus Group Discussions (FGDs), which address the rationale behind encouraging visitors to manage their own waste, facilitated by a dedicated team. Through FGDs, complemented by educational materials on the environmental impact of plastic waste and the development of a Procedural Manual for establishing a visitor littering control system, along with continued support, the park management succeeded in creating an environment where staff systematically and collectively persuade visitors while providing waste bags (disposal points) to prevent littering. The results of this initiative demonstrate that the visitor littering control system in the Mangrove Tourism Park has begun to take shape, characterized by a shared commitment and awareness to tackle waste management issues, as well as an increased understanding among the park management of the environmental hazards posed by plastic waste.